How were Half-Moons on Shells Made in the Upper Palaeolithic? An Experimental Approach - Annamaria Daniele (EXARC Journal, 2023)
In the Upper Palaeolithic levels of the site of Grotta Continenza (Abruzzo, Italy), numerous shells shaped as half-moons have been found. These artifacts, being important examples of ancient ornaments, have been regularly subjects of study, but the production process has only been hypothesised. This research, with the support of an experimental protocol, presents a possible manufacturing sequence for their creation.